Autologous serum implementation in treating ophthalmology patients - Stanković Bratislav; Petrović Jelena; Vujović Zorica; Popović Jovan; Trišović Marija (Halo 194, 2019)
Introduction/objective Autologous transfusion (AT) of blood and/or blood products is more and more commonly used in clinical practice. In ophthalmology, autologous serum (AS) prepared from autologous blood of the patient is commonly used to treat various diseases of the eye, expecially the dry eye syndrome. The objective of the research was to determine the importance of autologous serum implementation in treating eye disease, to establish the implementaion protocol in clinical practice, as well as to analyse the effects of the therapy in patients with various eye conditions. Methodology When prescribed by an ophthalmologist, AS is prepared for a particular patient following a strict preparation protocol. The Clinical Center of Serbia Eye Clinic implements its own modified procedure in preparing AS. From January 1st 2014 until December 31st 2018 540 patients (262-49% men and 278-51% women) have been admitted and treated using AS at the Eye Clinic. Results In 430 (80%)patients, the implementation of AS was initiated during hospitalization, to be continued after discharge and monitored regularly at checkups. In 110 (20%)patients, the AS therapy was initiated at the infirmary to be continued at home after the patient had been adequately educated to implement it correctly. Of all the patients treated with AS, the greatest number suffered from chemical injury of the eye (178 - 33%), a slightly smaller number (148 - 27%) from mechanical injury of the eye and 78 (15%) patients suffered from the dry eye syndrome. The study noted that the first effects of the therapy became evident after two weeks. The effects of the therapy were monitored using objective tests to evaluate the quality of the tear film (Schirmer I test, Rose Bengal test) and by evaluating the precorneal tear film breakup (Tear Break-Up Time - TBUT). The AS therapy can last from a few weeks to a few years. The patients report for check up once a week at the Eye Clinic. Conclusion The AS therapy is a cheap and simple procedure, efficient in treating difficult cases of dry eye syndrome, chemical and thermal eye injury. Preparation and implementation of AS is an activity that must be performed while strictly following rules and standards, which enables the implementation of a standard operative procedure.